Oxidoreductase protein family interaction with DJ-1 and oxidative stress-induced modulation of HADHA interactome - Ferreira, Andreia Sofia da Costa de Mónica (2016)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.